Management of aneurysmal subarachnoid hemorrhage with surgical clipping: A single center perspective - Küçükyıldız, Halil Can; Özüm, Ünal (Journal of Surgery and Medicine, 2022)
Background/Aim: There is no consensus on the optimal treatment for intracranial aneurysm rupture due to subarachnoid hemorrhage (SAH). In this study, we analyzed a series of ruptured intracranial aneurysms treated with the clipping method at our center. Methods: In this retrospective cohort study; we searched our patient database for patients who developed SAH due to ruptured intracranial aneurysm treated at the Neurosurgery Clinic of Sivas Cumhuriyet University. A total of 304 patients who underwent the clipping operation due to aneurysmal SAH between 2010 and 2020 were included in the study. Cases with aneurysmal SAH who underwent endovascular coiling which is consisted of 22 patients were excluded. Results: A significant inverse correlation was found between age and Glasgow coma scores (GCS) (r=−0.137, P=0.017). Hunt–Hess and Fisher grades increased significantly with increasing age (r=0.187, P<0.001 and r=0.185, P<0.001). The mean age of men was significantly lower than that of women (P=0.005). Aneurysms located in the anterior communicating artery were significantly more frequent in men than in women (P<0.001). There was no significant difference in the distribution of other aneurysm locations by gender (P>0.05). No significant differences were observed in GCS scores and Hunt–Hess and Fisher grades between genders (P>0.05). There were no significant effects of aneurysm locations on mortality (P>0.05). Conversely, GCS scores were significantly lower and Hunt–Hess and Fisher grades were significantly higher in the surviving group than in the deceased group (P<0.001). Conclusion: Our study presented the outcomes of patients treated in our clinic with surgical clipping. Based on our findings, we believe that surgical clipping is still a safe and valid treatment method.